Pengaruh Lama Fermentasi Bahan Organik Pada Eco-Enzyme Terhadap Daya Hambat Bakteri Staphylococcus aureus - Mutiara Nur Suci Febrianti; Inur Tivani; Susiyarti Susiyarti (Unversitas Muhammadiyah Mataram, 2024)
Abstract: Skin diseases are one of the most common most common health problems in Indonesia. One of the bacteria causing skin disease is Staphylococcus aureus. Eco-enzyme is an organic liquid resulting from the fermentation of organic waste, water and molasses sugar. This study aims to determine the effect of the length of fermentation of eco-enzyme organic material on the inhibitory activity activity and to find out the best fermentation time of eco-enzyme in inhibiting Staph bacteria. best in inhibiting Staphylococcus aureus bacteria. Research This research was conducted with a laboratory experimental approach using the simple random sampling method. Samples of eco-enzyme fermented for 3 months, 4 months and 5 months were tested for antibacterial activity against the growth of Staphylococcus aureus bacteria by the well diffusion method with aquadest as negative control. The results of the research data were analyzed statistically analyzed using One Way Anova test. Antibacterial test results of eco-enzyme that has been fermented for 3 months, 4 months, and 5 months inhibits the the growth of Staphylococcus aureus bacteria with an average inhibition zone of 13.73 mm, 17.73 mm, and 5 mm, respectively. 13.73 mm, 17.73 mm, and 21.4 mm, respectively. Based on this study, eco-enzyme fermentation time is proven to inhibit Staphylococcus aureus bacteria. aureus. Eco-enzyme that had the best bacterial inhibition was the eco-enzyme fermented with is eco-enzyme fermented for 5 months with an average inhibition zone of 21.4 mm. inhibition zone of 21.4 mm.Abstrak: Penyakit kulit menjadi salah satu dari berbagai masalah kesehatan yang paling banyak dijumpai di Indonesia. Salah satu bakteri penyebab penyakit kulit adalah bakteri Staphylococcus aureus. Eco-enzyme merupakan cairan organik hasil fermentasi limbah organik, air dan gula molase. Penelitian ini bertujuan untuk mengetahui pengaruh lama fermentasi bahan organik eco-enzyme terhadap aktivitas daya hambat yang dihasilkannya serta mengetahui waktu fermentasi eco-enzyme yang paling baik dalam menghambat bekteri Staphylococcus aureus. Penelitian ini dilakukan dengan pendekatan eksperimen laboratorium menggunakan metode simple random sampling. Sampel eco-enzyme yang di fermentasi selama 3 bulan, 4 bulan dan 5 bulan diuji aktivitas antibakterinya terhadap pertumbuhan bakteri Staphylococcus aureus dengan metode difusi sumuran dengan aquadest setril sebagai kontrol negatif. Hasil data penelitian dianalisis secara statistik menggunakan uji One Way Anova. Hasil uji antibakteri eco-enzyme yang telah difermentasi selama 3 bulan, 4 bulan, dan 5 bulan menghambat pertumbuhan bakteri Staphylococcus aureus dengan rata-rata zona hambat masing-masing 13,73 mm, 17,73 mm, dan 21,4 mm. Berdasarkan penelitian ini, waktu fermentasi eco-enzyme terbukti dapat menghambat bakteri Staphylococcus aureus. Eco-enzyme yang memiliki daya hambat bakteri paling baik yaitu eco-enzyme yang difermentasi selama 5 bulan dengan rata-rata zona hambat sebesar 21,4 mm.